Penerapan Model Pembelajaran Make a Match untuk Meningkatkan Motivasi Belajar Siswa Kelas IV MI Miftahul Ulum Kraton pada Tema 6 - Rizka Dewi Kurnia Sari; Moch. Bahak Udin By Arifin (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
future. Learning is closely related to how a teacher creates a pleasant learning atmosphere by applying learning models, one of which is the make a match type. The purpose of this study was to determine the application of the make a match type of cooperative learning method to increase the learning motivation of fourth grade students at MI Miftahul Ulum Kraton on Theme 6 and how effective the application of the method was. The method used in this research is the Classroom Action Research method. The research was conducted on fourth grade students of MI Miftahul Ulum Kraton. The results of the study concluded that first, the application of the make a match learning model was carried out by applying the second cycle where the first cycle in the observation results obtained an average percentage from 73.87% to 82.56% in the second cycle with an increase of 10.78%. on the results of the first cycle of the questionnaire, the average percentage increase was 4.538% from 71.782% in the first cycle to 76.32% in the second cycle. Second, the effectiveness of applying the make a match type of cooperative learning model to students is considered to be able to improve the learning process and increase the learning motivation of fourth grade students at MI Miftahul Ulum Kraton on theme 6.